Green Marketing and ICSR: The Influence of Brand Image on Purchase Decision Products PT. Paragon Technology Innovation - Putri Syalwa, Fitria; Saniatun Nurhasanah (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Ponorogo, 2025)
Introduction: This research aims to find out how green marketing, Islamic corporate social responsibility, and brand image influence purchase decision PT. Paragon Technology Innovation Product. Research Methods: This research uses a quantitative descriptive approach with primary data as the data used. The source of data collected use purposive sampling technique, came from distributing questionnaires to respondents in the Jabodetabek area through the consument of PT. Paragon Technology Innovation. The analysis technique used is Partial Least Square - Structural Equation Modeling (PLS-SEM). Results: Green marketing does not have a significant effect on the purchase decision of PT. Paragon products in the Jabodetabek area. Green marketing has a significant positive effect on the brand image of PT. Paragon products in the Jabodetabek area. Islamic corporate social responsibility has a significant positive effect on the purchase decision of PT. Paragon products in the Jabodetabek area. Islamic corporate social responsibility has a significant positive effect on the brand image of PT. Paragon products in the Jabodetabek area. Brand image has a significant positive effect on the purchase decision of PT. Paragon products in the Jabodetabek area. Conclusion: Based on the results of the study above, the following conclusions can be drawn: green marketing has no significant effect on purchase decisions on PT. Paragon Technology Innovation products; green marketing has a positive and significant effect on brand image on PT. Paragon Technology Innovation products; Islamic corporate social responsibility has a positive and significant effect on purchase decisions on PT. Paragon Technology Innovation products; Islamic corporate social responsibility has a positive and significant effect on brand image on PT. Paragon Technology Innovation products; brand image has a positive and significant effect on purchase decisions on PT. Paragon Technology Innovation products.